Low‐resolution colonic manometry leads to a gross misinterpretation of the frequency and polarity of propagating sequences: Initial results from fiber‐optic high‐resolution manometry studies. Issue 10 (17th June 2013) - Dinning, P. G.; Wiklendt, L.; Gibbins, I.; Patton, V.; Bampton, P.; Lubowski, D. Z.; Cook, I. J.; Arkwright, J. W.
Abstract Background High‐resolution manometry catheters are now being used to record colonic motility. The aim of this study was to determine the influence of pressure sensor spacing on our ability to identify colonic propagating sequences (PS). Methods Fiber‐optic catheters containing 72–90 sensors spaced at 1 cm intervals were placed colonoscopically to the cecum in 11 patients with proven slow transit constipation, 11 patients with neurogenic fecal incontinence and nine healthy subjects. A 2 h section of trace from each subject was analyzed. Using the 1 cm spaced data as the gold standard, each data set was then sub‐sampled, by dropping channels from the data set to simulate sensor spacing of 10, 7, 5, 3, and 2 cm. In blinded fashion, antegrade and retrograde PS were quantified at each test sensor spacing. The data were compared to the PSs identified in the corresponding gold standard data set. Key Results In all subject groups as sensor spacing increased; (i) the frequency of identified antegrade and retrograde PSs decreased (P < 0.0001); (ii) the ratio of antegrade to retrograde PSs increased (P < 0.0001); and (iii) the number of incorrectly labeled PSs increased (P < 0.003). Conclusions & Inferences Doubling the sensor spacing from 1 to 2 cm nearly halves the number of PSs detected. Tripling the sensor spacing from 1 to 3 cm resulted in a 30% chance of incorrectly labeling PSs. Closely spaced pressure recording sites (<2 cm) are mandatory to avoid gross misrepresentation of the frequency, morphology, and directionality of colonic propagating sequences.